Evolution of precision agricultural technologies: a patent network analysis - Tey, Yeong Sheng; Brindal, Mark; Wong, Seng Yee; Ardiansyah; Ibragimov, Abdulla; Yusop, Mohd Rafii (Springer, 2024)
Innovations in precision agriculture continue to increase in both number and significance. Contemporaneously, given their expanding scope and application, the growing pool of technologies is increasingly complex. Although some recent attempts have been made, a knowledge gap remains in respect to the evolution of precision agricultural innovation. Synthesized, such knowledge should inform the untapped opportunities for innovation. This paper narrows this gap by conducting a network analysis of patent applications in areas concerning precision agriculture. Spanning the years from 1960 to 2021, the analysis shows an annual average growth in patent applications of 15.1. During the last decade, this growth is almost entirely attributable to China and the USA. Priority innovation themes have been dynamic. Its phases can be characterized as ‘motorized mechanization’ (1960–1999), ‘mechanical automation’ (2000–2009), ‘digital mechanization’ (2010–2019), and ‘digital automation’ (2020–2021). The significance of information communication technology has grown in association with other innovation clusters, but a lag time has persisted in introducing innovations based on such technologies. Opportunities are ripe for speeding transference through economic and other incentives.